2004
DOI: 10.1051/vetres:2004039
|View full text |Cite
|
Sign up to set email alerts
|

Biotin-avidin amplified ELISA for detection of antibodies to Sarcoptes scabiei in chamois (Rupicapra spp.)

Abstract: -Scabies is a major threat to the well being of mountain-dwelling Bovid hosts, Rupicapra rupicapra and Rupicapra pyrenaica. Severe outbreaks are in progress over a significant part of their distribution area and resource managers demand improved methods to monitor, analyse and possibly forecast the spread and effects of scabies at the population level. An amplified capture enzyme-linked immunosorbent assay was developed to detect antibodies to Sarcoptes scabiei in chamois (Rupicapra spp.) serum. The method use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
(37 reference statements)
1
34
0
2
Order By: Relevance
“…serum [31]. This assay, the first one designed for the detection of S. scabiei in a freeranging ruminant host, used a whole body extract of the various developmental stages of S. scabiei as antigen, obtained from skin lesions of naturally infected red foxes (Vulpes vulpes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…serum [31]. This assay, the first one designed for the detection of S. scabiei in a freeranging ruminant host, used a whole body extract of the various developmental stages of S. scabiei as antigen, obtained from skin lesions of naturally infected red foxes (Vulpes vulpes).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than 50% of skin scrapes can be negative in canine scabies infections [24]. In recent years, many enzyme-linked immunosorbent assays (ELISA), based on crude mite extracts have been developed for several host species [6,7,13,31,36]. S. scabiei is the source of multiple antigenic molecules [1][2][3] and the varieties of S. scabiei from different animals introduce both cross-reactive and variety specific antigens into the host [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Biotin-avidin binding is commonly used in immunohistological staining of singular proteins and in biochemical assays such as for enzyme-linked-immuno-absorption (Rambozzi et al 2004). However, biotin-avidin has not been assessed in the context of utilizing ampliWcation of one protein to avoid cross-reactivity with alternate antigenantibody complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Severe outbreaks are in progress over a significant part of their distribution areas, and resource managers demand improved methods to monitor, analyze, and possibly forecast the spread and effects of sarcoptic mange at the population level (Rambozzi et al 2004). Unfortunately, we could not determine the source of exposure in this case, but it seems that the close contact of the gazelles with domesticated animals or rodents could be the main source of exposure.…”
Section: Resultsmentioning
confidence: 99%